Process planning and scheduling for loop layout robotic workcell using virtual reality technology - Yap, Hwa Jen; Tan, Chee Hau; Phoon, Sin Ye; Liew, Kan Ern; Chandra Sekaran, Sivadas (SAGE Publications, 2019)
The adoption of virtual reality in manufacturing system simulation had proved its effectiveness in bridging up to the gap between different areas of expertise, especially in product design and manufacturing. Virtual reality had enclosed human–machine interface by enabling the user to be immersed into the virtual environment and experience real-time interaction with the virtual objects. In this article, an implementation of virtual reality in cellular manufacturing system simulation is presented. By utilizing the features of visualization and real-time interaction of virtual reality technology, the manufacturing process of a product had been visualized while the real-time control on the product traveling path based on the user’s input was performed and the corresponding activities that related to the change of traveling path had been predicted in the virtual environment. Through the study, simulation of the manufacturing system in virtual reality showed its potential as a powerful decision support system in process planning and scheduling. Various process planning and schedules can be planned through the virtual environment, while the product traveling distance can be obtained from the developed system. © The Author(s) 2019.